PEMBELAJARAN BACAAN SHOLAT LIMA WAKTU BERBASIS ANIMASI INTERAKTIF - HENNY DESTIANA; ABDUL ROSID (LPPM Universitas Bina Sarana Informatika, 2015)
Rapid technological developments affecting the role of a computer itself. At first only focused on the use of computer data processing, but along with the advancement of technology today use computers not only focused on data processing, but also serve as a medium of information in various fields one of which is education.Utilization of the computer as a medium of learning in education has begun to be used in the TPQ (The Learning Quran). As a teacher in a TPQ, the computer can be used as a medium in the teaching and learning process which has the function as a media tutorial, as learning tools and test equipment that will be very helpful in the process of storage and an understanding of the material presented.One of the educational material should be taught to children include religious education. Especially for the Moslem prayer is the pillar of religion. Early on children should begin to be taught about prayer because it is one obligation for Muslims.Based on the above background, the authors took the initiative to create interactive animations guidance prayer. With this application is expected to provide benefits and knowledge to children about prayer guidance of animation and drawings on the theme of children, so that children who learn quickly not saturated in the study as a means of self-learning children.E